Assessment of Seismic Bearing Capacity of a Strip Footing Resting on Reinforced Earth Bed using Pseudo-Static Analysis - Jaiswal, Sagar; Chauchan, Vinay Bhusan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The use of geosynthetic reinforcement to enhance the ultimate load-bearing capacity and reduce the anticipated settlement of the shallow foundation has gained sufficient attention in the geotechnical field. The improved performance of the shallow foundation is achieved by providing one or more layers of geosynthetics below the foundation.
Keywords: reinforced earth; bearing capacity; strip footing; Finite Element Method (FEM); pseudo-static analysis; wzmocnienie podłoża; nośność; ława fundamentowa; metoda elementów skończonych; analiza pseudostatyczna